2018
DOI: 10.1007/978-3-319-89884-1_23
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Design Tradeoffs in Numeric Static Analysis for Java

Abstract: Abstract. Numeric static analysis for Java has a broad range of potentially useful applications, including array bounds checking and resource usage estimation. However, designing a scalable numeric static analysis for real-world Java programs presents a multitude of design choices, each of which may interact with others. For example, an analysis could handle method calls via either a top-down or bottom-up interprocedural analysis. Moreover, this choice could interact with how we choose to represent aliasing in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…The impact of different abstract-interpretation configurations has been previously evaluated [54] for Java programs and partially inspired this work. To the best of our knowledge, we are the first to propose tailoring abstract interpreters to custom usage scenarios using optimization.…”
Section: Related Workmentioning
confidence: 99%
“…The impact of different abstract-interpretation configurations has been previously evaluated [54] for Java programs and partially inspired this work. To the best of our knowledge, we are the first to propose tailoring abstract interpreters to custom usage scenarios using optimization.…”
Section: Related Workmentioning
confidence: 99%
“…First, T P over-approximates formulas translated from the assembly, but E does not have front ends supporting SMTLIB2 or assembly. Second, E requires a third-party pointer analysis to reason about aliasing, which is a source of imprecision [Wei et al 2018]. While in the assembly-level symbolic execution, such information has been precisely and implicitly encoded in the formulas.…”
Section: Polyhedra Abstractionmentioning
confidence: 99%
“…Wei et al [307] evaluated different program analyses, including representations for integers and heap abstractions. They and we both found that polygons are expensive and not very helpful; simpler analyses can suffice.…”
Section: Related Work: Array Boundsmentioning
confidence: 99%